Etiology and prognostic evaluation of malignant pleural effusion - Ramesh, Sadhana; Hazarika, Basanta; Sarma, Jogesh; Karwa, Rahul (International Journal Of Community Medicine And Public Health, 2020)
Background: Malignant pleural effusion is a common medical problem in patients with cancer. The survival of patients with malignant pleural effusion is generally poor. The objectives of our study were to reveal possible prognostic factors of malignant pleural effusion. Methods: Fifty-three consecutive patients, 34 male and 19 female patients of malignant pleural effusion diagnosed by pleural fluid positive for malignant cytology and/or pleural tissue positive for malignancy by thoracoscopy biopsy. Performance status by the Eastern Cooperative Oncology Group (ECOG) score and LENT score was calculated at the time of diagnosis. Median survival time was calculated using Kaplan-Meier analysis curve. Survival time was defined as the time from diagnosis to death or the last follow-up. Results: Most common cause of malignant pleural effusion was lung carcinoma 46 (86.79%). Adenocarcinoma was the most common 31 (58.5%) followed by NSCLC 10 (18.0%). Low, moderate and high-risk LENT score was found in 3 (5.7%), 35 (66%) and 15 (28.3%) respectively. The median survival time of pleural fluid sugar less than 20 were 3 months. The median survival time of LENT low, medium and high risk was 12 months, 5.2 months and 2.5 months respectively. The median survival time of patients with ECOG score of 1 and 4 was 6.5 months and 1 month respectively. Patients with bilateral pleural fluid had a mean survival time of 2 months. Conclusions: Adenocarcinoma lung is the most common etiology of malignant pleural effusion. The median overall survival time was 4 months. Higher ECOG score and LENT score are associated with shorter survival time.